Análise da influência do sombreamento causado pelos edifícios na zona central de Curitiba - Campos, Giovana de Almeida Coelho (2014)
Urban growth and the fast pace in the concentration of people in cities are inevitable. Building verticalization as a solution to attend the need of maximum land use and to justify the infrastructure invested by the government in central areas, cause considerable impacts on the environment which they are. However, urbanization is not a problem itself, but how cities are being built and occupied. Thus, the main goal of this work is to verify the shadow influence caused by tall buildings in a specific area inside of the zone with more capacity of verticalization in Curitiba. This research was developed in four steps: the first one was to study the existing literature about this topic, second to define study section in the city and periods to be analyzed, third step to delimit a zoom of study with analysis about all periods and, fourth with computer simulations on Auto CAD, Sketchup Pro, Excel and Ecotect softwares to obtain important results. During the evolution of this work, it was verified that the shading caused by tall buildings undertake considerably neighboring buildings and all surrounding area. Furthermore, it was concluded that Curitiba, a cold city, suffers in winter season due to excessive shading in public spaces between blocks. On the other hand, open spaces as squares are correctly positioned and do not harm with verticalization on the downtown zone. Anyway, the intention to reduce the impact caused by these processes must be planned in a more embracing context. Project elaboration must consider local climate and urban context, just as the environmental impacts of those on neighboring buildings and on open spaces. The idea of preserving skylines already consolidate, avoiding tall buildings, can be an alternative to minimize shading impacts.